HIV Drug Resistance after Failure of 6 Month First-line Therapy in a Hospital: A Case Series - Ardiana Kusumaningrum; Fera Ibrahim; Evy Yunihastuti; Budiman Bela (Acta Medica Indonesiana, 2019)
This is the first report of HIV drug resistance in RSUPN Dr. Cipto Mangunkusumo. We tested We reviewed eleven new cases of HIV patients who had virologic failure after 6 months first-line antiretroviral therapy. With the sequencing method, analysis of gene mutations encoded HIV drug resistance. Genotypic resistance results and HIV-1 subtype were interpreted by Stanford DR database. Of ten plasma samples that were successfully amplified and sequenced, all samples were resistant to at least one antiretroviral drug. Genotypic resistance towards the antiretroviral drugs being used was observed in lamivudine (90%), tenofovir (83%), nevirapine (100%) dan efavirenz (100%). It is interesting that no zidovudine resistance were found, including in four patients receiving zidovudine in their HAART. The common NRTI mutations were M184VI and K65R, while NNRTI mutations were Y181CFGVY, K103N, A98AG, E138GQ and G190AGS. No mayor PI mutations were found. Based on these findings, we supports the need for appropriate virology monitoring and HIV drug resistance survey in clinical practice and access to drug options in case of virology failure.